Ethnoracial Diversity and Critical Human Resource Development (CHRD) : The Case Against Racial Colorblindness in the Workplace - Osmar, Warsame (2020)
Abstract German health care is facing the challenges arising from the recruitment of a diversified workforce that includes foreign-born and foreign-trained (FB&FT) physicians, which may differ from Germany’s autochthonous majority White population. This implies the presence of a notable diversity category in the workplace: “race/ethnicity.” In business, (racial) differences seem to go unnoticed. The notion of “not seeing race” or adopting a colorblind racial ideology (CBRI) seems to be the emerging approach to manage racial diversity in the workplace. Thus, this dissertation investigates the ways in which institutional structures in Germany, which maintain the colorblind status quo, contribute to racial inequality. Drawing on the precepts for human resource development (HRD) along with its investigative critical dimension (critical HRD), this thesis aims to highlight the racialized experiences of both White and non-White participants as a means of combating and eliminating workplace prejudice and inequalities. To do so, I conducted 33 semi-structured interviews with FB&FT physicians including 14 non-Caucasians/Whites to analyze how “race/ethnicity” and “racism” are conceptualized within the health care professional and policy discourse. I employed a constructivist approach to grounded theory for qualitative analyses. Second, using statistical regression models, I empirically examined racial colorblindness in the German context. The investigation comprised 136 autochthonous adults and “individuals with migration backgrounds” residing in Bavaria, who were divided by self-identified race (85 Whites, 51 non- Whites). The results of the qualitative study revealed that participants offered a critical analysis of race-related terms, but there was a disparity in understanding of racial concepts between Caucasian/White physicians and non-Caucasian/White physicians.